Effectiveness of Article 40 Paragraph (1) of PP Number 24 of 1997 Concerning the Obligation of PPAT to Submit Deeds Made to the Land Office - Octaviani, Irva; Widyanti, Yenny Eta; Susilo, Hariyanto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2025)
Article 40 paragraph (1) of Government Regulation Number 24 of 1997 regulates the obligation of Land Deed Making Officials (PPAT) to submit the deeds they have made to the Land Office within 7 (seven) working days. However, in practice, this provision is often not implemented in a timely manner, resulting in various administrative and legal obstacles. This study aims to analyze the effectiveness of the implementation of Article 40 paragraph (1) of PP No. 24 of 1997 at the Pulang Pisau Regency Land Office. The method used is an empirical legal approach with data collection through surveys and interviews. The results of the study indicate that there are still delays in the submission of deeds by PPAT, one of which is in the case of the Deed of Granting Mortgage Rights which was registered almost two months after signing. This delay has an impact on the slow process of recording rights and issuing certificates, as well as reducing legal certainty for the community. The main causal factors include lack of supervision, low administrative sanctions, and technical obstacles on the part of PPAT. In conclusion, the implementation of Article 40 paragraph (1) has not been effective and requires strengthening of regulations and increasing legal awareness for PPAT.